Pengaruh Pemberian Edukasi Terhadap Pengetahuan Kader Kesehatan - Vicky Arfeni Warongan; Vikri Syahaikal; Juni Arnita (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The prevalence of non-communicable diseases (NCDs) and their risk factors continue to increase in Indonesia. Riskesdas 2018 showed an increase in the main indicators of NCDs, such as hypertension, obesity, and smoking habits. The low knowledge of health workers, patients, and the community about NCDs is often the cause of the difficulty in controlling the disease, especially blood pressure. Knowledge can be increased by several factors, including age and understanding of mindset. This study aims to identify the impact of education on increasing the knowledge of health cadres. The method used is quantitative with a pre-experimental design, using a one group pre-test and post-test approach. A sample of 10 individuals was selected using the total sampling method. Data were collected through questionnaires before and after providing education about Posbindu NCDs and non-communicable diseases of hypertension and diabetes mellitus. The analysis was carried out univariately, and after the normality test showed that the pre-test and post-test data were normally distributed, the Paired sample t-test was carried out. The results showed that almost half of the respondents were between 41-50 years old (50%), and more than half of the respondents had a senior high school education level (80%). The Paired sample t-test produced p-value of 0.001 which is smaller than 0.05. In conclusion, there is a significant effect of providing education on increasing the knowledge of health cadres. Further training is needed to improve the understanding and skills of health cadres.